Composition for β-spodumene formation and heat-resistant clay material

JP2026169336APending Publication Date: 2026-10-16WITEN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026183749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-02-21
Filing Date
2026-08-04
Publication Date
2026-10-16

Smart Images

  • Figure 2026169336000001_ABST
    Figure 2026169336000001_ABST
Patent Text Reader

Abstract

The present invention provides a material that can form a calcined body containing a β-spodumene phase, achieving excellent low expansion properties while using stably available raw materials. [Solution] This heat-resistant clay raw material contains a lithium salt and clay, and when fired, forms a fired body containing a β-spodumene phase. The lithium salt is aluminum-free or has an aluminum content of 0.1% by mass or less. The clay is present in an amount of 20% by mass or more of the total raw material, and the lithium salt is present in an amount of 0.1% to 25% by mass of the total raw material. Furthermore, this raw material contains 0.01% to 45% by mass of fused silica relative to the total composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a composition for forming a β-spodumene phase, and to a heat-resistant clay raw material for forming a fired body containing a β-spodumene phase. [Background technology]

[0002] While ceramic sintered bodies generally have high melting points and excellent heat resistance, materials such as alumina and zirconia have relatively large coefficients of thermal expansion. For this reason, lithium-based silicate sintered bodies such as β-spodumene (Li2O·Al2O3·4SiO2) and β-eucryptite (Li2O·Al2O3·2SiO2) are used in applications such as heat treatment jigs where thermal shock resistance is required. Furthermore, in applications such as heat-resistant tableware and cookware like earthenware pots, as well as roof tiles and bricks, sintered bodies are used in which petalite (Li2O·Al2O3·8SiO2), a natural lithium ore, is mixed with clay, and then heat-treated to generate a β-spodumene phase, thereby reducing thermal expansion.

[0003] Here, since petalite has an extremely low lithium content, it is necessary to add a large amount of petalite to improve thermal shock resistance. In contrast, as a method for producing the β-spodumene phase without using petalite, for example, the technology described in Patent Document 1 has been proposed. Patent Document 1 proposes a technology for producing β-spodumene by calcining natural spodumene (Li2O·Al2O3·4SiO2) at approximately 1100 to 1350°C and causing its crystal structure to undergo an α-β transformation. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 4-65315 [Overview of the project] [Problems that the invention aims to solve]

[0005] However, since Japan relies heavily on imports for most of its minerals, their availability is subject to change due to fluctuations in resource conditions. In particular, in recent years, there has been an increasing trend of restrictions on the export of unprocessed ore that has not undergone certain processing (e.g., calcination or refining), which could make it difficult to obtain unprocessed ore such as petalite and alpha-spodumene in the future.

[0006] This invention was made in view of the above background, and aims to provide a material that can form a calcined body containing a β-spodumene phase that achieves excellent low expansion properties while using stably available raw materials. [Means for solving the problem]

[0007] The present invention relates to a β-spodumene-forming composition comprising a lithium salt and clay, wherein a calcined body containing a β-spodumene phase is formed by calcination, characterized in that the lithium salt is aluminum-free or has an aluminum content of 0.1% by mass or less, and the lithium salt is present in an amount of 0.01 to 30% by mass relative to the entire composition.

[0008] Furthermore, the β-spodumene-forming composition of the present invention is characterized by containing fused silica, wherein the fused silica is present in an amount of 0.01 to 45% by mass relative to the entire composition.

[0009] Furthermore, the β-spodumene-forming composition of the present invention is characterized in that the lithium salt is lithium carbonate.

[0010] The heat-resistant clay raw material of the present invention comprises a lithium salt and clay, and is characterized in that it forms a fired body containing a β-spodumene phase when fired, wherein the lithium salt is aluminum-free or has an aluminum content of 0.1% by mass or less, the clay is present in an amount of 20% by mass or more of the total heat-resistant clay raw material, and the lithium salt is present in an amount of 0.1 to 25% by mass of the total heat-resistant clay raw material.

[0011] Furthermore, the heat-resistant clay raw material of the present invention is characterized in that it contains fused silica, and the fused silica is present in an amount of 0.01 to 45% by mass relative to the entire composition.

[0012] Furthermore, the heat-resistant clay raw material of the present invention is characterized in that the lithium salt is lithium carbonate.

[0013] Furthermore, the heat-resistant clay raw material of the present invention is characterized by containing at least one additive selected from iron oxide, pyrophyllite, feldspar, chamotte, dolomite, lime, talc, magnesite, alumina, petalite, cordierite, barium compounds, and strontium compounds.

[0014] Furthermore, the fired body of the above heat-resistant clay raw material of the present invention has a thermal expansion coefficient of 5.0 × 10⁻⁶ from room temperature to 700°C. -6 It is characterized by being less than or equal to / K.

[0015] The ceramics of the present invention are heat-resistant ceramics which are fired bodies of heat-resistant clay raw materials, and the heat-resistant clay raw material is the heat-resistant clay raw material described above. [Effects of the Invention]

[0016] The β-spodumene-forming composition of the present invention comprises a lithium salt and clay, and is a composition that forms a calcined body containing a β-spodumene phase by calcination. The lithium salt is aluminum-free or has an aluminum content of 0.1% by mass or less, and the lithium salt is present in an amount of 0.01 to 30% by mass of the total composition. Therefore, a calcined body containing a β-spodumene phase can be obtained without using lithium ore. In another embodiment, this composition contains fused silica, and since the fused silica is present in an amount of 0.01 to 45% by mass relative to the entire composition, the coefficient of thermal expansion can be reduced. Furthermore, since the lithium salt is lithium carbonate, it offers excellent handling, safety, and availability.

[0017] The heat-resistant clay raw material of the present invention comprises a lithium salt and clay, and is a heat-resistant clay raw material that forms a fired body containing a β-spodumene phase when fired, wherein the lithium salt contains no aluminum or has an aluminum content of 0.1 mass% or less, the clay is contained in an amount of 20 mass% or more relative to the entire raw material, and the lithium salt is contained in an amount of 0.1 to 25 mass% relative to the entire raw material. Accordingly, a fired body containing a β-spodumene phase and having excellent low expandability can be obtained without using lithium ore. In another aspect, this raw material contains fused silica, and the fused silica is contained in an amount of 0.01 to 45 mass% relative to the entire raw material, so that the coefficient of linear expansion can be further reduced. In addition, since the lithium salt is lithium carbonate, it is excellent in handleability, safety, availability and the like.

[0018] Further, the heat-resistant clay raw material contains at least one additive selected from iron oxide, pyrophyllite, feldspar, chamotte, dolomite, lime, talc, magnesite, alumina, petalite, cordierite, barium compounds, and strontium compounds, so that various characteristics can be imparted to the sintered body.

[0019] Since the ceramic of the present invention is a fired body of the above-described heat-resistant clay raw material of the present invention, it is a product containing a β-spodumene phase that achieves excellent low expandability, using stably available raw materials without relying on conventional expensive petalite. Therefore, it can be suitably used, for example, as tableware or cooking utensils for direct flame use. [Brief Description of the Drawings]

[0020] [Figure 1] It is a diagram showing the results of the X-ray diffraction pattern of Example 8. [Figure 2] It is a diagram showing the results of the X-ray diffraction pattern of Example 9. [Figure 3] It is a diagram showing the results of the X-ray diffraction pattern of Comparative Example 1. [Mode for Carrying Out the Invention]

[0021] The β-spodumene-forming composition and heat-resistant clay raw material of the present invention are compositions and raw materials that contain clay and a predetermined lithium salt, and form a calcined body containing a β-spodumene phase by calcination.

[0022] β-spodumene is a tetragonal lithium-based aluminosilicate with the composition Li2O·Al2O3·4SiO2, and the β-spodumene phase is its crystalline phase (also called a β-spodumene solid solution) that precipitates in the calcined body. Because the β-spodumene phase is a crystalline phase with low thermal expansion, the thermal expansion of the calcined body can be reduced by forming (precipitating) the β-spodumene phase in the calcined body. This low coefficient of thermal expansion is thought to be due to the anisotropy of the crystal axis direction and the presence of microcracks that accompany it. Microcracks are more likely to occur when the anisotropy in the crystal axis direction is greater.

[0023] The precipitation of the β-spodumene phase can be confirmed by X-ray diffraction. In X-ray diffraction, for example, using CuKα rays, the diffraction pattern is obtained by measuring the Bragg angle (2θ) in the range of 10° to 80°, and the precipitated crystals can be identified when diffraction peaks appear. In the X-ray diffraction pattern, β-spodumene is a crystal that generally shows diffraction peaks at Bragg angles (2θ) of 25.55°±0.05°, 22.71°±0.05°, and 28.20°±0.05°. Based on the pattern (chart) obtained by X-ray diffraction, the presence or absence of the β-spodumene phase can be confirmed by analyzing the crystal structure using standard identification methods (Hanawald method or Rietveld method) provided with the instrument, referring to PDFs (Powder Diffraction File) provided by ICDD (International Centre for Diffraction Data).

[0024] In general, clay materials and glazes used in ceramics and porcelain are mixed with naturally occurring lithium ores such as petalite and α-spodumene. By firing these mixtures, a crystalline phase of β-quartz solid solution is produced, or even a more stable crystalline phase of β-spodumene solid solution, ensuring low thermal expansion (thermal shock resistance) for the entire fired or molded body. Such ceramics are widely available as lithium-based (Li2O-Al2O3-SiO3) heat-resistant pottery. However, as mentioned above, in recent years, the availability of unprocessed ores has become increasingly limited, and there is a risk that obtaining unprocessed ores such as petalite and α-spodumene may become difficult in the future. Therefore, using relatively readily available raw materials as raw materials for low-expansion molded bodies that form β-spodumene is extremely important from the perspective of securing stable raw materials. In this invention, by using a predetermined lithium salt (such as lithium carbonate) as a lithium source, it is possible to form a β-spodumene phase and achieve low expansion even without using minerals such as petalite mentioned above.

[0025] The β-spodumene-forming composition and heat-resistant clay raw material of the present invention comprises clay and a predetermined lithium salt. The clay used in this invention is a soil component formed from clay minerals containing silica and alumina, and examples include clays containing kaolin minerals (kaolin such as kaolinite, kifushi clay, kaolinite, dickite, nacrite, halloysite, New Zealand kaolin, Korean kaolin, and Hadong kaolin), and sericite. These clays may be used individually or in combination of two or more. The silica and alumina components contained in these clays serve as sources of aluminum and silicon when forming the β-spodumene phase (Li2O·Al2O3·4SiO2).

[0026] In the β-spodumene-forming composition of the present invention, the content of clay relative to the total β-spodumene-forming composition is not particularly limited, as long as it is an amount that enables the formation of β-spodumene. For example, the content of clay relative to the total β-spodumene-forming composition can be adjusted to 1-99% by mass, 5-95% by mass, 10-90% by mass, 20-80% by mass, 30-70% by mass, etc.

[0027] In the heat-resistant clay raw material of the present invention, the content of clay relative to the total heat-resistant clay raw material is set to 20% by mass or more, taking into consideration sufficient low thermal expansion and moldability, in addition to enabling the formation of β-spodumene. By setting it within this range, it is possible to mold it into the shape of a product while ensuring low thermal expansion (thermal shock resistance). The content of clay relative to the total heat-resistant clay raw material can be adjusted to, for example, 20-98% by mass, 30-95% by mass, 30-90% by mass, 30-80% by mass, 30-70% by mass, 30-60% by mass, 30-55% by mass, 40-50% by mass, etc.

[0028] The lithium salt used in this invention is preferably a lithium salt obtained by purification or synthesis, rather than a mineral-based lithium salt. Mineral-based lithium salts contain alumina and silica. Therefore, the lithium salt used in this invention does not contain aluminum (Al), or has an aluminum content of 0.1% by mass or less. The aluminum content is expressed as a mass percentage of the total mass of the lithium salt in terms of metallic aluminum, in the case of aluminum in an oxide state (alumina: Al2O3), etc. If aluminum is present, it is more preferable that its content is 0.01% by mass or less.

[0029] Examples of lithium salts include lithium carbonate (Li2CO3), lithium chloride (LiCl), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), lithium hydroxide (LiOH), and lithium citrate. Among these, lithium carbonate is preferred due to its superior handling, safety, and availability. Lithium carbonate may be a secondary material produced by extraction and purification from lithium minerals, or it may be recycled lithium carbonate recovered and purified after industrial use.

[0030] The lithium salt is included in powder (particulate) form. The average particle size of the lithium salt is not particularly limited. Examples of usable average particle sizes of lithium salt include 1-500 μm, 1-100 μm, 1-50 μm, 5-100 μm, 5-50 μm, 5-30 μm, 10-100 μm, 10-50 μm, and 10-30 μm. The particle size of the lithium salt is preferably determined considering the reactivity that contributes to the formation of the β-spodumene phase, the mechanical strength of the calcined body, and the effect on microcracks (low thermal expansion). In this invention, 1-100 μm is preferred, and 1-50 μm is more preferred.

[0031] In this invention, "average particle diameter" refers to the particle diameter (D50) when the particle diameter distribution (particle size distribution) is measured using a known particle size distribution analyzer (for example, a laser diffraction particle size distribution analyzer), and the frequency (%) of the particle diameters is accumulated from the smallest particle diameter to the largest.

[0032] In the β-spodumene-forming composition of the present invention, the content of lithium salt relative to the total β-spodumene-forming composition is 0.01 to 30% by mass. By keeping it within this range, β-spodumene can be precipitated during calcination. The content of lithium salt relative to the total β-spodumene-forming composition can be adjusted to, for example, 0.01 to 28% by mass, 0.01 to 25% by mass, 0.1 to 30% by mass, 0.1 to 28% by mass, 0.1 to 25% by mass, 0.5 to 30% by mass, 0.5 to 28% by mass, 0.5 to 25% by mass, 1 to 30% by mass, 1 to 28% by mass, 1 to 25% by mass, 3 to 30% by mass, 3 to 28% by mass, 3 to 25% by mass, 5 to 30% by mass, 5 to 28% by mass, 5 to 25% by mass, etc.

[0033] In the heat-resistant clay raw material of the present invention, the content of lithium salt relative to the total heat-resistant clay raw material is 0.1 to 25% by mass. By keeping it within this range, it is possible to suppress cracking during firing while ensuring low thermal expansion (thermal shock resistance). The content of lithium salt relative to the total heat-resistant clay raw material can be adjusted to, for example, 0.3 to 25% by mass, 0.5 to 25% by mass, 1 to 25% by mass, 2 to 25% by mass, 3 to 25% by mass, 5 to 25% by mass, etc.

[0034] The β-spodumene-forming composition and heat-resistant clay raw material of the present invention may contain fused silica. The inclusion of fused silica may contribute to a reduction in the thermal expansion coefficient of the fired body. This may be due to the physical properties of fused silica itself (low expansion), or it may be due to its effect on the formation of the β-spodumene phase. Furthermore, the inclusion of fused silica can relatively reduce the amount of lithium carbonate in the composition / raw material required to ensure the desired low thermal expansion.

[0035] The fused silica used in this invention is a type of silica with a low coefficient of thermal expansion, unlike crystalline quartz or crystal. Examples of fused silica that can be used in this invention (also called quartz glass, fused silica, or silica glass) include powder obtained by rapidly cooling and solidifying crystal or quartz at high temperatures using an oxyhydrogen flame, electricity, or plasma arc, and then crushing it, or obtained by chemical vapor deposition or the sol-gel method. Since fused silica is manufactured artificially in this way, it can be obtained stably. As a result, a stable supply of the β-spodumene-forming composition and heat-resistant clay raw materials of this invention becomes possible.

[0036] Compositions and raw materials containing a large amount of natural ingredients may experience variations in composition due to the natural ingredients. Therefore, from the standpoint of product quality stability, it is desirable to use fused silica, which is artificially manufactured and has less variation in composition, to achieve durability and appearance equivalent to or better than conventional products. Here, a characteristic of fused silica produced by a method of melting quartz and other materials at high temperatures using electricity (hereinafter referred to as the "electric melting method") is that it contains almost no OH groups (hydroxyl groups) which have the effect of reducing heat resistance. As a result, fused silica produced by the electric melting method has superior heat resistance compared to fused silica obtained by other manufacturing methods.

[0037] Crystalline quartz (silica) is found in feldspar and other raw materials and is widely used as a raw material for ceramics. The main reasons for mixing quartz into clay and glaze are to improve the strength and luster of the ceramics after firing. However, most naturally occurring quartz is crystalline, and its inclusion increases the coefficient of thermal expansion. In contrast, fused silica is amorphous and, as mentioned above, is a raw material with a low coefficient of thermal expansion. By keeping at least a portion of the fused silica unmelted during firing, excellent thermal shock resistance can be achieved. Furthermore, when fused silica produced by the electrofusion method is used, as mentioned above, it has excellent heat resistance, making it easier for a portion of the fused silica to remain unmelted.

[0038] Fused silica is included in particulate form. The average particle size of the fused silica is not particularly limited. Examples of usable average particle sizes of fused silica include 0.01 to 5.00 mm, 0.01 to 1.00 mm, 0.01 to 0.80 mm, and 0.01 to 0.50 mm. Alternatively, two or more types of fused silica with different average particle sizes may be mixed and used. When the particle size of the fused silica is within the above range (0.01 to 5.00 mm), a good balance is achieved between melting near the particle surface and non-melting in the particle center during the firing of the composition / raw materials, which tends to improve the thermal shock resistance and toughness of the fired body, leading to improved bending strength.

[0039] In the β-spodumene-forming composition and heat-resistant clay raw material of the present invention, the content of fused silica relative to the total composition / raw material is 0.01 to 45% by mass. By setting it to 0.01% by mass, it is possible to improve low thermal expansion (thermal shock resistance). Furthermore, by setting it to 45% by mass or less, cracking during firing after drying can be suppressed. The content of fused silica relative to the total composition / raw material can be adjusted to, for example, 0.1 to 45% by mass, 1 to 45% by mass, 3 to 45% by mass, 5 to 45% by mass, 1 to 35% by mass, 5 to 35% by mass, 5 to 15% by mass, etc.

[0040] The heat-resistant clay raw material of the present invention may contain additives known in general heat-resistant ceramic raw materials. Examples of additives include iron oxide, pyrophyllite, feldspar, chamotte, dolomite, lime, talc, magnesite, alumina, petalite, cordierite, barium compounds, and strontium compounds. These may be used individually or in combination of two or more. Among these, the addition of iron oxide, pyrophyllite, feldspar, and chamotte is preferred. Iron oxide (ferric oxide) is used for coloring and strength improvement, pyrophyllite is used as a lubricant, feldspar is used for polishing, chamotte is used as a cushioning material during firing, and petalite and cordierite are used as low-expansion materials. These additives may also be added to the β-spodumene-forming composition of the present invention.

[0041] Examples of iron oxides include ferrous oxide (FeO), ferric oxide (Fe2O3), and triiron tetroxide (Fe3O4). Examples of ferric oxides include NAT iron oxide, HRT iron oxide, NSK iron oxide, and red iron oxide.

[0042] When petalite is included as a low-expansion additive, it is added in small amounts and is not included as a lithium source for the formation of the β-spodumene phase. Cordierite (2MgO·2Al2O3·5SiO2) is a magnesium-containing silicate mineral. In addition, other low-expansion additives such as mullite (3Al2O3·2SiO2), zircon (ZrO2·SiO2), and borosilicate glass (Na2O-B2O3-SiO2) may be added.

[0043] In addition, sodium silicate and bentonite may be added as additives. Bentonite and sodium silicate are used as viscosity improvers and are effective in suppressing cracks when the base material is molded and dried. In particular, bentonite is effective in improving viscosity even when added in small amounts; for example, even if the content ratio of bentonite to the total heat-resistant clay raw material is 1% by mass, a significant improvement in viscosity can be achieved.

[0044] The content of additives relative to the total heat-resistant clay raw material can be adjusted to, for example, 0.1-30% by mass, 0.1-20% by mass, 0.1-10% by mass, 0.1-8% by mass, 0.1-6% by mass, or 0.1-5% by mass in total. When feldspar is added as an additive, as mentioned above, the feldspar raw material contains crystalline quartz, which may increase the coefficient of linear expansion. Therefore, the feldspar content is preferably 15% by mass or less (for example, a lower limit of 0.1% by mass) and more preferably 10% by mass or less (for example, a lower limit of 0.1% by mass) relative to the total composition / raw material.

[0045] The firing temperature range for firing the β-spodumene-forming composition and heat-resistant clay raw material of the present invention can be adjusted to, for example, 1000-1400°C, 1000-1300°C, 1000-1250°C, 1100-1400°C, 1100-1300°C, 1100-1250°C, etc. Firing at 1000°C or higher allows for sufficient precipitation of the β-spodumene phase. Firing at 1400°C or lower allows for sintering without completely melting the molten silica present. The firing time can also be adjusted as appropriate. Furthermore, the firing conditions can be oxidation firing or reduction firing, and either condition may be used.

[0046] The ceramics of the present invention are fired bodies made from the heat-resistant clay raw material of the present invention. Heat-resistant ceramics are manufactured by the following main steps: (A) forming clay made from heat-resistant clay raw material, (B) applying glaze to the surface of the molded clay body as needed, and (C) firing in a firing furnace and then cooling in the furnace.

[0047] In the molding process of (A), predetermined amounts of each mineral constituting the heat-resistant clay raw material are mixed. This mixing can be done using either the known wet or dry method. If mixed using the wet method, the mixture (slip) is dehydrated and caked to become clay for molding. The material is molded after kneading. Molding methods that can be used include roller machine molding, press molding, pressure casting (compression) molding, slip molding, water trowel molding, hand kneading, and slab molding, and the material is molded into predetermined shapes such as earthenware pots and plates. Note that the heat-resistant clay raw material can be either red clay or white clay.

[0048] The glazing process in (B) is performed as needed. In this process, the surface of the molded body formed in process (A) is glazed. Any glaze that can form a glassy glaze layer can be used. Glazing methods such as dipping and spraying can be used to glaze the surface of the molded body.

[0049] In the firing process of (C), the molded body obtained above is placed in a gas kiln or electric kiln and fired under the above firing conditions, for example, at a temperature of 1000 to 1400°C. The firing time is approximately 1 to 24 hours. By firing at a temperature of 1400°C or lower, sintering can be achieved without completely melting the molten silica, as described above. The firing conditions may be either oxidation firing or reduction firing. Oxidation firing is a method in which a large amount of air (oxygen) is supplied into the kiln and firing is carried out under conditions where sufficient oxygen is present. Reduction firing is a method in which wood, coal, gas, etc., are introduced into the kiln to the extent that incomplete combustion occurs and firing is carried out.

[0050] Furthermore, in the molding process of (A), the heat-resistant viscosity raw material may be pre-fired. For example, a heat-resistant viscosity raw material from which a portion of the clay content has been removed from the final composition can be used, pre-fired to form a β-spodumene phase, and this molded product can be crushed or otherwise processed, and then clay can be mixed and kneaded in the manner described above to obtain the final composition before molding. In this case, adhesion to the mold during molding can be suppressed. Note that the pre-fired product may be fired at a temperature lower than the firing temperature, for example, at a temperature of 500°C or higher. The upper limit temperature for pre-fired is not particularly limited, but for the same reasons as in the firing process of (C), it is preferable to fire at a temperature of 1400°C or lower.

[0051] This pre-firing differs from the calcination process before the glazing process (B), which is common in ceramics. It is a process that partially promotes the formation of β-spodumene in the material before molding. As a result, as described above, the effect of suppressing adhesion to the mold during molding is obtained. In addition, regardless of whether or not this pre-firing is performed, a general calcination process may be carried out before the glazing process (B). The calcination process is carried out at a temperature of, for example, 700 to 1100°C.

[0052] The ceramic of the present invention can be manufactured to meet the standard of a temperature difference of 350°C or higher specified in JIS S 2400 based on the Industrial Standardization Act for factories certified by the Ministry of Economy, Trade and Industry when exposed to an open flame. In particular, by blending lithium carbonate into clay to form a β-spodumene phase, and blending fused silica, the resulting heat-resistant ceramic has excellent low thermal expansion property (thermal shock resistance) as the entire ceramic, is resistant to open flames, and has practically sufficient durability.

[0053] The fired body of the heat-resistant clay raw material preferably has a linear expansion coefficient of 5.0×10 from room temperature to 700°C -6 / K or less. It is more preferably 4.0×10 -6 / K or less, still more preferably 3.5×10 -6 / K or less, still more preferably 3.0×10 -6 / K or less, still more preferably 2.5×10 -6 / K or less, still more preferably 2.0×10 -6 / K or less. In addition, the linear expansion coefficient may be a negative value. Therefore, the linear expansion coefficient preferably falls within each of the above ranges as an absolute value.

[0054] Further, the difference in linear expansion coefficient measured under the same temperature conditions in the case of reduction firing and oxidation firing is preferably -1.0 to 1.0×10 -6 / K. It is more preferably -0.8 to 0.8×10 -6 / K, still more preferably -0.5 to 0.5×10 -6 / K. By setting the difference in linear expansion coefficient within the range of ±1.0×10 -6 / K, sufficient low expansion property (thermal shock resistance) can be obtained regardless of the firing conditions. [Examples]

[0055] Examples 1 to 26, Comparative Example 1 The compositions shown in Table 1 were prepared, and predetermined test specimens were molded using these compositions. The specimens were then fired at 1200°C for 20 hours in an oxidizing atmosphere to produce the test specimens. Korean kaolin was used as the clay. Commercially available lithium carbonate (white powder, purity 99.9%, Al content 0.001% by mass or less, average particle size 1-100 μm) was used as the lithium carbonate. Commercially available fused silica (average particle size 0.01-5.00 mm) was used as the fused silica. The silica was crystalline silica. The coefficient of linear expansion of these test specimens was measured using a thermomechanical analyzer, heated from room temperature (25°C) to 700°C at a heating rate of 7°C / min. The results are shown in Table 1.

[0056] [Table 1]

[0057] As shown in Table 1, the coefficient of thermal expansion was 5.0 × 10⁻⁶ for all test specimens used in the test. -6 The coefficient of thermal expansion was below / K, and a decrease in the coefficient of thermal expansion was confirmed compared to the case of clay alone (Comparative Example 1).

[0058] Next, the crystalline phases of Example 8 (5% by mass lithium carbonate, 95% by mass clay), Example 9 (5% by mass lithium carbonate, 90% by mass clay, 5% by mass fused silica), and Comparative Example 1 (100% by mass clay) were identified using an X-ray diffraction analyzer. The results of the X-ray diffraction patterns are shown in Figure 1 (Example 8), Figure 2 (Example 9), and Figure 3 (Comparative Example 1), respectively. The Rigaku "RINT2500" analyzer was used, and the qualitative analysis software "JADE5" was used.

[0059] As shown in Figures 1 and 2, the composition containing lithium carbonate showed a β-spodumene phase peak (JCPD-ICDD:35-0797) that could not be seen in Figure 3. Furthermore, as shown in Table 1 above, the actual coefficient of thermal expansion in Examples 8 and 9 was significantly reduced compared to Comparative Example 1. [Industrial applicability]

[0060] The β-spodumene-forming composition and heat-resistant clay raw material of the present invention are materials that can form fired bodies containing a β-spodumene phase that achieves excellent low expansion properties while using stably available raw materials. Therefore, they can be stably mass-produced and widely used as raw materials for industrial and household materials that require a low coefficient of linear expansion. In particular, they can be suitably used as heat-resistant ceramics such as tableware and cookware for direct flame use.

Claims

1. A composition comprising a lithium salt and clay, which forms a calcined body containing a β-spodumene phase upon firing, The lithium salt is a lithium salt that does not contain aluminum, or has an aluminum content of 0.1% by mass or less. A composition for forming β-spodumene, characterized in that the lithium salt is contained in an amount of 0.01 to 30% by mass relative to the entire composition.

2. The composition for forming β-spodumene according to claim 1, characterized in that the composition comprises fused silica, wherein the fused silica is present in an amount of 0.01 to 45% by mass relative to the entire composition.

3. The β-spodumene-forming composition according to claim 1 or 2, characterized in that the lithium salt is lithium carbonate.

4. A heat-resistant clay raw material containing a lithium salt and clay, which forms a calcined body containing a β-spodumene phase when fired, The lithium salt is a lithium salt that does not contain aluminum, or has an aluminum content of 0.1% by mass or less. The clay is present in an amount of 20% by mass or more relative to the total heat-resistant clay raw material. The heat-resistant clay raw material is characterized in that the lithium salt is contained in an amount of 0.1 to 25% by mass relative to the total heat-resistant clay raw material.

5. The heat-resistant clay raw material according to claim 4, characterized in that the heat-resistant clay raw material contains fused silica, and the fused silica is present in an amount of 0.01 to 45% by mass relative to the entire composition.

6. The heat-resistant clay raw material according to claim 4 or 5, characterized in that the lithium salt is lithium carbonate.

7. The heat-resistant clay raw material according to claim 4 or 5, characterized in that it contains at least one additive selected from iron oxide, pyrophyllite, feldspar, chamotte, dolomite, lime, talc, magnesite, alumina, petalite, cordierite, barium compounds, and strontium compounds.

8. The fired body of the aforementioned heat-resistant clay raw material has a coefficient of thermal expansion of 5.0 × 10 from room temperature to 700°C. -6 A heat-resistant clay raw material according to claim 4 or 5, characterized in that it is less than or equal to / K.

9. A ceramic product that is fired from heat-resistant clay raw materials, A ceramic product characterized in that the heat-resistant clay raw material is the heat-resistant clay raw material described in claim 4 or claim 5.

Citation Information

Patent Citations

  • Production of beta-spodumene

    JP1992065315A